Penerapan Manajemen Mutu Terpadu di Lembaga Pendidikan Swasta Islam: Resiliensi Terhadap Keterbatasan Anggaran - Muhammad Nur Ahsan; Siti Aimah (Southeast Asian Journal of Islamic Education Management, 2025)
This research is motivated by the demands of improving the quality of education in private educational institutions often faced with budget constraints. This study aims to analyze the impact of budget constraints on implementing Total Quality Management (TQM) and to identify effective and efficient TQM implementation strategies in these conditions. This study uses a qualitative approach with a case study type at SMP Queen Ibnu Sina, Banyuwangi. Data was collected through in-depth interviews with the principal, vice principal, teachers, and administrative staff, observation and documentation studies. The study's results indicate that budget constraints significantly impact initial TQM investments, such as staff training and system development, as well as on ongoing TQM maintenance, which led to the selection of more affordable internal evaluations. Nevertheless, the institution demonstrated resilience by implementing several adaptive strategies. Prioritizing areas for improvement is the primary strategy. Creative use of internal resources has also proven effective. External collaboration with MGMP, professional organizations, and the government opens up access to resources and expertise that are difficult to reach independently. Strong leadership, staff commitment, effective communication, budget transparency, ongoing evaluation, and a culture of continuous improvement are also necessary. The study concluded that TQM implementation can still be effective in private institutions with limited budgets through adaptive strategies such as prioritization, utilization of internal resources, and external collaboration, supported by strong leadership and an organizational culture that supports improvement.